PENGEMBANGAN MASYARAKAT MELALUI TEKNOLOGI TEPAT GUNA (TTG) MELALUI PELATIHAN PERKOPERASIAN BAGI KELOMPOK TANI MULTIGUNA BINA USAHA SUKSES DI DESA SUNGAI MENGKUANG KABUPATEN BUNGO - Suliska, Gita; Girsang, Ronald N; Ferdian, Tommy (EDUTECH CONSULTANT, 2019)
This community service aims to enable the Successful Multipurpose Farmer Group to Build a Successful Business in Sungai Mengkuang Village, Bungo Regency, to be able to establish a Cooperative and to be able to carry out their own bookkeeping in order to conduct their financial records so that their expenses and income can be measured and the benefits obtained. The target of the service is the Multipurpose Farmer Business Development Group Success in Sungai Mengkuang Village, Bungo Regency. The training was carried out using the training method with a presentation method followed by question and answer discussion and case studies. Results of bookkeeping training activities for the perpetrators of Successful Multipurpose Farmer Development Groups in Sungai Mengkuang Village, Bungo District This financial bookkeeping training shows there is a positive response from the actors or participants so that the trainees can understand the procedures for establishing a Cooperative, the benefits of the Cooperative and improving their skills and knowledge of business actors and can make good financial reports.